Helicobacter pylori infection and peptic ulcer in eastern Turkish children: Is it more common than known? - (:unkn) unknown (My University, 2011)
Helicobacter pylori (H. pylori) infection is mainly acquired in childhood and is frequent in developing countries. The infection is associated with chronic gastritis in all infected children, but peptic ulcer disease develops in a small number of them. In our country, H. pylori infection and associated peptic ulcer disease are common. In eastern Turkey, we found peptic ulcer disease in 13.2% of children who underwent endoscopic examination. Peptic ulcers were mostly gastric ulcers and H. pylori-positive in the studied population, and most of the children were admitted due to abdominal pain. As there are no well-established criteria leading directly to diagnosis, pediatricians should include H. pylori infection and peptic ulcer disease in the differential diagnosis list when evaluating children with abdominal pain, failure to thrive and upper gastrointestinal system bleeding.
Keywords: Children; Helicobacter pylori; Peptic ulcer disease